Structural contracts and liability concerns associated with building information modeling - Boos, Peter Edward (Kansas State University, 2010)
Building Information Modeling (BIM) is altering the way that the construction industry is developing design documents by involving all members of the design team as well as the general contractor early in the design process. The members are encouraged to offer advice on the design and constructability on the project. However, not only is the design process changing, but the liability and responsibility of each team member is changing as well. The alteration in responsibility can severely impact structural engineers because of the level of responsibility already associated with their role in the design process. This report looks at the concerns industry leaders and legal professionals have with how BIM is altering the liability landscape, such as standard contracts, software interoperability, data misuse, intellectual property, loss of data, the legal status of the model, the standard of care, and design delegation. In addition to the liability concerns, this report examines the steps that industry leaders have taken to prevent any unnecessary additional liability from affecting structural engineers.
Keywords: Liability; Building Information Modeling (BIM); Contracts; Structural; Engineering; Legal; Engineering, Civil (0543); Engineering, General (0537); Law (0398)